2013
DOI: 10.3389/fnhum.2013.00570
|View full text |Cite
|
Sign up to set email alerts
|

The time course of reading processes in children with and without dyslexia: an ERP study

Abstract: The main diagnostic criterion for developmental dyslexia (DD) in transparent orthographies is a remarkable reading speed deficit, which is often accompanied by spelling difficulties. These deficits have been traced back to both deficits in orthographic and phonological processing. For a better understanding of the reading speed deficit in DD it is necessary to clarify which processing steps are degraded in children with DD during reading. In order to address this question the present study used EEG to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
95
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(112 citation statements)
references
References 115 publications
(275 reference statements)
13
95
3
1
Order By: Relevance
“…Jost, Raith, & Maurer, 2014). Moreover, another result supporting the claim that the N1 reflects a specific brain training effect comes from studies with populations of different reading expertise: the N1 response is attenuated in groups lacking reading expertise such as dyslexic children (Araújo, Faísca, Bramão, Petersson, & Reis, 2012;Hasko, Groth, Bruder, Bartling, & Schulte-Körne, 2013; and adults Mahé, Bonnefond, Gavens, Dufour, & Doignon-Camus, 2012). This finding indicates that perceptual coding of orthographic properties might be compromised in dyslexia, contributing to a deficient development of automatic and fluent reading.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…Jost, Raith, & Maurer, 2014). Moreover, another result supporting the claim that the N1 reflects a specific brain training effect comes from studies with populations of different reading expertise: the N1 response is attenuated in groups lacking reading expertise such as dyslexic children (Araújo, Faísca, Bramão, Petersson, & Reis, 2012;Hasko, Groth, Bruder, Bartling, & Schulte-Körne, 2013; and adults Mahé, Bonnefond, Gavens, Dufour, & Doignon-Camus, 2012). This finding indicates that perceptual coding of orthographic properties might be compromised in dyslexia, contributing to a deficient development of automatic and fluent reading.…”
Section: Introductionsupporting
confidence: 57%
“…One set of studies described similar brain activation patterns for words and pseudowords observed around the peak of the N1 (Araújo et al, 2012;Bentin et al, 1999;Hasko et al, 2013;Kast, Elmer, Jancke, & Meyer, 2010;Maurer et al, 2005), and no modulation by different levels of word frequency (Araújo et al, 2012). These findings suggest that the N1-evoked response might arise at the earliest prelexical stages of the orthographic system.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations